2013
DOI: 10.1080/17571472.2013.11493361
|View full text |Cite
|
Sign up to set email alerts
|

What kind of leadership does integrated care need?

Abstract: This was an education paper which did not involve primary data collection so did not need ethical committee approval

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Participants acknowledged the need for future leadership to implement change through ‘soft power’, recognise the need to work across boundaries and build relationships and enable organisations to develop cultures that support collaboration within the system [50]. Such leaders of transformation would guide rather than control [51] and be willing to ‘give away ownership’ [50]. The present study found the issue of system leadership was a significant barrier to achieving integrated care and supports previous research which recognises ‘that effective system leadership is a necessary prerequisite to achieving truly effective care co-ordination’ [52].…”
Section: Discussionmentioning
confidence: 99%
“…Participants acknowledged the need for future leadership to implement change through ‘soft power’, recognise the need to work across boundaries and build relationships and enable organisations to develop cultures that support collaboration within the system [50]. Such leaders of transformation would guide rather than control [51] and be willing to ‘give away ownership’ [50]. The present study found the issue of system leadership was a significant barrier to achieving integrated care and supports previous research which recognises ‘that effective system leadership is a necessary prerequisite to achieving truly effective care co-ordination’ [52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the structure was developed by a group of tenants and employees, supported by mutual experts. Mutuals need to emerge from the grassroots, but they also need a leadership style (very much the leadership style described by Deirdre Kelley-Patterson) 6 which nurtures and supports engagement at a grassroots level, specifically in order to harness the knowledge and experience of those closest to the problems in finding appropriate solutions. It is engagement and participation in problem-solving, based on ownership, which provide a strong contrast to other forms of transfer out of state ownership.…”
Section: A Social Housing Case Study For New Mutualismmentioning
confidence: 99%
“…One certainty in an era of uncertainty is that this traditional outsider status is no longer tenable. 8 For the sake not only of its existence but also for that of the Triple Aim itself, family physicians must emerge as thought and delivery system leaders in our health system 9,10 Recognizing both the backdrop of change and uncertainty and the new roles demanded of its diplomates, the American Board of Family Medicine (ABFM) anchored its strategic planning on several core principles, which included the following statements:…”
mentioning
confidence: 99%